Anatomía y usos de la madera de ocho especies tropicales de Quintana Roo, México - Rebollar, Silvia; Quintanar, Alejandra (Revista de Biología Tropical, 1998)
This paper describes the wood anatomy of Acacia gaumeri Blake, Diphysa carthagenensis Jacq., Gliricidia sepium (Jacq.) Steud., Leucaena glauca (L.) Benth., Senna racemosa (Mill) Irwin & Bameby, Murraya paniculata L.Mant., Maytenus guatemalensis Lundell; and Pimenta dioica (L.) Merr. These species are aesthetically attractive as well as hard, highly durable and resistant to insects and locally are widely used in posts, fences, sleepers and rural buildings. Samples were collected from the rainfores! in Quintana Roo, Mexico. One tree for each species was collected, and macroscopic and microscopic characteristics were described and measured in wood samples, perrnanent slides and macerated material. Woods have diffuse porosity, simple perforation plates, alternate and opposite vessel pits and small rays. Crystals are absent only in Acacia gaumeri and Senna racemosa. Axial parenchyma aliforrn paratracheal, banded types and líbriforrn tibres were cornmon. Differences were found in rays, pore arrangement, presence of fibrotracheids, vascular tracheids and tylos